STUDI TINGKAT BAHAYA EROSI BERDASARKAN PENGGUNAAN LAHAN PADA SATUAN BENTUK LAHAN VULKANIK DI JALAN SIMPANG AMPEKâTALU KECAMATAN TALAMAU KABUPATEN PASAMAN BARAT - Susilawati, Susilawati; Edial, Helfia; Farida, Farida (STKIP PGRI Sumbar, 2013)
This research was conducted with the aim of ; 1) Determine the level of erosion hazard based on slope unit of land form unit in Jalan Simpang Ampek â Talu Talamau District, 2) Knowing the rate of erosion on the density of the vegetation cover unit of land based unit of land form in the Jalan Simpang Ampek â Talu Talamau District, 3) Knowing the rate of erosion rainfall based on land form unit in Jalan Simpang Ampek â Talu Talamau District, 4) Knowing the rate of erosion on the use of land based on land form unit in Jalan Simpang Ampek â Talu Talamau District. Existing units of land in the study area consists of land 48 land units and samples were taken only 4 units of land.Techniq to take sample with purposive sampling manner deliberately, the researchers determine their own samples taken based on the certain considerations. This study classified as descriptive research. Descriptive research is a research procedure that uses descriptive data in the form of words written or spoken of the people and actors that can be observed. The research focus on the actual problems that have happened and what the data is desired without manipulated.The results showed that the rate of erosion differ based on the use of land in the units of land on volcanic hills (V3) ; 1) The potential erosion contained in the class II midle category where the risk of erosion are there, but rarely found in sample 1 V3.III.Pm.Tmv.Lat driving factor is the slope of erosion and precipitation and sample 2 at V3.III.Sw.Tmv.Lat driving factor is the rainfall erosion, 2) Of potential erosion class III contained in the high category where the risk of high attrition, erosion often found in sample 3 at V3.III.Kc.Tmv.Lat is the driving factor of slope erosion, vegetation density land cover and rainfall and sample 4 at V3.III.Ht.Tmv.Lat is the driving factor of slope erosion, vegetation density land cover and rainfall.Â Â Â Â Â Â Â Â Â Â